Analisis Kesehatan Bank pada Unit Usaha Syariah (UUS) di Masa Pandemi Covid-19 dengan Menggunakan Metode RGEC - Iqbal Rafiqi; Siti Halimah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
Abstrak This study aims to determine the soundness of sharia business units (UUS) registered with the Islamic Financial Services Authority for 2019-2021 using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, and Capital). This research method used in research is descriptive quantitative method. The results of this study using the RGEC method resulted in an Assessment of Bank Soundness in Indonesian Sharia Business Units (UUS) for 2019-2021 in terms of the Risk Profile factor with an average NPL yielding a value of 3.00% indicating that the bank is in good health, while the average LDR value produces 96,03% which indicates that the bank is in a fairly Enought healthy condition, Good Corporate Governance from the self-assessment results, namely obtaining an average of 2, which indicates the bank is in good health, Earning an average ROA produces a value of 1.17% indicating that the bank is in Enought healthy condition, with an average ROE value of 8,58% indicating that the bank is in an unhealthy state, and with an average BOPO yielding a value of 65,57% indicating that the bank is in very good health and Capital with an average CAR yields a value of 23,96% which indicates that the bank is in very good health.